2016
DOI: 10.1080/02678292.2016.1189001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and liquid crystalline behaviour of substituted (E)-phenyl-4-(phenyldiazenyl) benzoate derivatives and their photo switching ability

Abstract: Azobenzene derivatives containing phenyl/4-halogen-phenyl 4-{(E)-[4-(pent-4-en-1-yloxy)phenyl] diazenyl}benzoate group with different electronegative substituent (H, F, Cl, Br and I) at other end was synthesised. These azo-based benzoate derivatives have been characterised by FTIR, 1 H-NMR, 13 C-NMR, elemental analyser, POM and UV-Vis spectroscopy. Photosaturation at 358 nm obtained after 82 s of UV irradiation and the longest thermal back relaxation time of 45 h recorded by UV-Vis. The azo derivative could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…14,15 In addition, azobenzene derivatives have been proposed for potential applications in the areas of nonlinear optics, 16 chemo sensors, 17 liquid crystals, 18 photochemical molecular switches, 19 molecular shuttles 20 and drug delivery. 21 Recently, we have designed and studied the optical storage properties of several azobenzene derivatives, namely, the azobenzene dimers with aromatic and aliphatic spacers, 22 uorinated azobenzene esters, 23 photopolymerizable azobenzene derivatives, 24 bent-shaped azobenzene monomers, 25,26 alkoxy azobenzene derivatives with coumarin moieties, 27 siloxane based azobenzene derivatives, 28 hydrophilic/ hydrophobic-based azobenzene mesogens 29 and amide functionalized azobenzene derivatives with intermolecular Hbonding. 30 The presence of an electronegative moiety in the case of amide containing azobenzene units leads to another possibility of a weak hydrogen bonding due to the lone pair of electrons present on electronegative atom.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 In addition, azobenzene derivatives have been proposed for potential applications in the areas of nonlinear optics, 16 chemo sensors, 17 liquid crystals, 18 photochemical molecular switches, 19 molecular shuttles 20 and drug delivery. 21 Recently, we have designed and studied the optical storage properties of several azobenzene derivatives, namely, the azobenzene dimers with aromatic and aliphatic spacers, 22 uorinated azobenzene esters, 23 photopolymerizable azobenzene derivatives, 24 bent-shaped azobenzene monomers, 25,26 alkoxy azobenzene derivatives with coumarin moieties, 27 siloxane based azobenzene derivatives, 28 hydrophilic/ hydrophobic-based azobenzene mesogens 29 and amide functionalized azobenzene derivatives with intermolecular Hbonding. 30 The presence of an electronegative moiety in the case of amide containing azobenzene units leads to another possibility of a weak hydrogen bonding due to the lone pair of electrons present on electronegative atom.…”
Section: Introductionmentioning
confidence: 99%
“…35 Table 1 shows the summary of time taken for the selected compounds for E-Z photoisomerisation with their calculated conversion efficiency (CE). 7 As shown in Table 1, 1a-8 took the longest time (157 s) for E-Z conversion with the CE of 27.3% aer exposure to UV light, whereas Ic-8 gave 45.1% of CE when bulky ferrocene was replaced by a benzene ring. However, Id-8, IV-8 and V-8 took shorter time (40-50 s) with the low CE of 8-10% aer introducing alkoxy chain in benzene ring.…”
Section: Photoisomerisation Studiesmentioning
confidence: 96%
“…ester, olenic, acetylenic, azo, imido) that maintains the linearity of the core. 5 Azobenzene, as one of the traditional photochromic moieties, is thermally very stable and can perform photo-induced reversible isomerization under UV irradiation, [6][7][8][9][10] So azo compounds have advantages over substances with other linkages like ester, tolane or even the more commonly encountered Schiff's base linkage. [11][12][13] In recent decades, azobenzene based low and high molecular weight liquid crystalline materials have been frequently discussed for their sensitivity of chromophoric group towards light and found to exhibit interesting optical properties, which enable us to study the materials in holography, optical storage device, optical switching and establish widespread applications in display technology.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work [25], it was observed that the mesophase stability is enhanced by an increment of the polarity and/or polarizability of the mesogenic core of the molecule. In general, the linking groups in the mesophase formation, type, thermal stability, and temperature ranges of the LCs compounds [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%